1901 Mich. Pub. Acts 687, Local Acts, no. 469, tit. 3, § 8, pt. 7. - (:unkn) unknown (General Publisher, 1901)
To regulate, restrain or prohibit the buying, selling, carrying, and using of firearms, weapons, gunpowder, firecrackers or fireworks manufactured or prepared therefrom, or from other combustible material, and the exhibition of fireworks, and the discharge of firearms, and the lights in barns, stables and other buildings, and to restrain and prohibit the making of bonfires in streets, yards, alleys and other public places.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION; DISCHARGE